2018
DOI: 10.1007/s00423-018-1716-8
|View full text |Cite
|
Sign up to set email alerts
|

Insurance status does not affect short-term outcomes after oncological colorectal surgery in Europe, but influences the use of minimally invasive techniques: a propensity score-matched analysis

Abstract: Background and Purpose Controversy exists whether surgical treatment is influenced by insurance status. American studies suggest higher morbidity and decreased survival in uninsured patients with colorectal cancer (CRC). It remains elusive, however, whether these findings apply to European countries with mandatory, government-driven insurance systems. We aimed to analyze whether operative techniques, quality of surgery, and complication rates differ among patients covered by statutory (SI) versus private (PI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, other groups and we have reported conversion rates e.g. for colectomy [28,40] and associated risk factors [63]. Lastly, national data of Switzerland might just be partly generalizable to other countries, especially with different healthcare systems.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, other groups and we have reported conversion rates e.g. for colectomy [28,40] and associated risk factors [63]. Lastly, national data of Switzerland might just be partly generalizable to other countries, especially with different healthcare systems.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, LOS observed in our study were longer then reported from large-scale retrospective series from other countries. Switzerland has traditionally longer LOS than other countries in Europe or in the US [28], an aspect which is attributed to regional and cultural traditions rather than medical necessities. Lastly, the observed decrease in LOS across 20 years was modest at best despite major advances in surgical care, changes in hospital reward policies and advent of enhanced recovery after surgery programs [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrast may be due to their smaller sample size (6000 vs. 30,000) or to a different patient population, as their study included only data from a level-one trauma centre. Another Swiss study on colorectal surgery also found no difference in complications between patients with state versus private healthcare insurance; however, the use of minimally invasive techniques was different in publicly and privately insured patients [ 30 ]. We must be aware that this data do not allow to control for a possible effect of over-treatment in patients with private insurance and to reassess the indications – at least the number of operations and length of stay were not significantly different in both insurance groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown a higher uptake of CRC surgery and use of minimally invasive techniques among privately versus publicly insured patients, even though postoperative complications and survival rates were comparable between the insurance types. 29,30 Moreover, data from the United States suggest that patients with CRC enrolled on Medicaid, which is a government-regulated insurance type, receive CRC treatments substantially less often and have lower survival than those with PHI. 31,32 However, whether and to what extent insurance type is associated with uptake of targeted therapy or survival in patients with stage IV disease is unclear but could be useful for determining factors associated with uptake of therapeutic innovations by insurance type in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%